Innovative technologies in teaching a foreign language - Natalia V. Ageyenko; Alla A. Rybkina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In the article, the necessity to introduce innovative educational technologies to improve the effectiveness of the learning process is actualized. It is noted that the use of innovative computer technologies is not only a means of gaining knowledge, but also a means of forming professional competencies. A number of modern methods of teaching a foreign language are distinguished and a description of the tasks of the Web technology quest is given in detail. The authors come to the conclusion that it is expedient to use web quests as one of the varieties of innovative technologies in the educational process, the effectiveness of which is confirmed by the growing cognitive activity of students, the possibility of individualizing the learning process, raising the level of socialization of future specialists, and the level of professional competence.